Please I need help I'm in grade 5 and I don't understand this so make me understand in a easy way.
9. If A = x - y + z, B = 2x - 3y +4z and C = 4x - 5y - 6z, find
(I) A + B + C
(II) A - B + C
(III) A + B - C​

Respuesta :

Answers:

  • A+B+C = 7x - 9y - z
  • A-B+C = 3x - 3y - 9z
  • A+B-C = -x + y + 11z

======================================================

Explanation:

Skip to the "Work Shown" section below to see the steps for each part.

Each variable is a place holder for some unknown number. We can think of it like a box that holds a number. Luckily the letter x is found in the word "box" to help cement this line of thinking.

1x = 1 box

2x = 2 boxes

3x = 3 boxes

and so on

This shorthand notation allows us to quickly add boxes

2 boxes + 3 boxes = 5 boxes

So 2x+3x = 5x

And we can subtract boxes as well

7 boxes - 3 boxes = 7x - 3x = 4x = 4 boxes

The same number must go in box x for this to work out.

When it comes to dealing with negative numbers, it might help to use a vertical number line. I like to think of it like going up and down an elevator on a skyscraper. Negative integers represent basement levels.

It's possible to have boxes within boxes. The box A has the three boxes x-y+z inside it. So wherever we see an "A", replace it with x-y+z. Unfortunately we don't know what numbers go in the boxes for x, -y and z. Use the same type of thinking for B and C.

Don't forget to use the distributive property to distribute the negative through to each term.

Example: (x+y)-(w+z) = x+y-w-z

Many students make the mistake in saying that (x+y)-(w+z) = x+y-w+z which is not true. The +z should be -z at the very end.

Let me know if you have any other questions.

The next section below shows the steps needed to get the three answers.

----------------

Work Shown:

Part (I)

A+B+C = (x-y+z)+(2x-3y+4z)+(4x-5y-6z)

A+B+C = (x+2x+4x)+(-y-3y-5y)+(z+4z-6z)

A+B+C = 7x - 9y - z

Part (II)

A-B+C = (x-y+z)-(2x-3y+4z)+(4x-5y-6z)

A-B+C = x-y+z-2x+3y-4z+4x-5y-6z

A-B+C = (x-2x+4x)+(-y+3y-5y)+(z-4z-6z)

A-B+C = 3x - 3y - 9z

Part (III)

A+B-C =  (x-y+z)+(2x-3y+4z)-(4x-5y-6z)

A+B-C =  x-y+z+2x-3y+4z-4x+5y+6z

A+B-C = (x+2x-4x)+(-y-3y+5y)+(z+4z+6z)

A+B-C = -x + y + 11z